Morphology Controllable Synthesis of NiO/NiFe2O4 Hetero-Structures for Ultrafast Lithium-Ion Battery - Wang, Ying; Wu, Shengxiang; Wang, Chao; Wang, Yijing; Han, Xiaopeng (Frontiers in Chemistry, 2019)
By combining advantages of hetero-structure and nano-architecture, a novel strategy to improve the rate performance and cycling stability of NiFe2O4 is proposed. Herein, a series of NiO/NiFe2O4 hetero-structures with tailored porosity, particle size, and shell/internal structure have been synthesized via a controllable annealing process. The optimized NiO/NiFe2O4 (S-NFO) is hierarchical hollow nanocube with ~5 nm subunits and high porosity. When being applied as anode for lithium storage, the S-NFO exhibits high rate capability and excellent cycle stability, which remains high capacity of 1052 mAh g-1 after 300 cycles at 5.0 A g-1 and even 344 mAh g-1 after 2000 cycles at 20 A g-1. Such impressive electrochemical performance of S-NFO is mainly due to three reasons. One is high porosity of its hierarchical hollow shell, which not only promotes the penetration of electrolyte, but also accommodates the volume change during cycling. Another is the small particle size of its subunits, which can effectively shorten the electron/ion diffusion distance and provide more active sites for Li+ storage. Besides, the hetero-interfaces between NiO and NiFe2O4 also contribute to faster charge transport.